Establishing an Efficient Regeneration System for Tissue Culture in Bougainvillea buttiana ‘Miss Manila’ - Tao Huang; Huihui Zhang; Runan Zhao; Zunling Zhu (Plants, 2022)
Bougainvillea plants have important ornamental and cultural value, as well as applications, for example, in improving the ecological environment, sterilization and as anti-virals in medicines, etc. Among many varieties, Bougainvillea buttiana ‘Miss Manila’ is more popular in landscape applications in southern China because of its excellent qualities. However, because of the difficulty of sexual reproduction, low rooting rate of asexual propagation cuttings and low temperature tolerance, its large-scale development is limited. For easy, quick and mass multiplication of such cultivars, tissue culture technique can be put to use. In this study, nodal segments of ‘Miss Manila’ were used as explants, and a single-factor experiment was carried out with a variety of plant growth regulators and concentrations to establish and optimize a complete tissue culture propagation system. The results showed that the best disinfestation was 75% ethanol treatment for 0.5 min + 0.1% HgCl2 treatment for 9 min, and the survival rate was 86.83%. The best shoot initiation formula was MS + 6-BA (2.5 mg/L) + IBA (0.2 mg/L), and the induction rate was 95.14%. The best formula for shoot proliferation was MS + 6-BA (1.5 mg/L) + NAA (0.1 mg/L), and the proliferation coefficient was 3.13. The best rooting culture formula was 1/2 MS + IBA (2.0 mg/L), and the rooting rate was 81.97%. The survival rate for plantlet refining and transplanting was 93.33%. In this study, a relatively efficient regeneration system for the tissue culture and rapid propagation of Bougainvillea buttiana ‘Miss Manila’ was established to address the problems of rooting and transplanting of this variety, to benefit research on the industrialized production and regeneration systems of this variety, and to provide a reference for the tissue culture of other varieties of Bougainvillea or other woody plants.